Synthesis of Rare Pentoses Using Microbial and Enzymatic Reactions - Li, Zijie; Gao, Xiao-Dong; Cai, Li (Current Organic Chemistry, 2016)
Rare pentoses, especially L-rare pentoses, have been attracting increasing attention because of their medicinal applications in antiviral and anticancer therapy, where they are used to produce L-nucleoside analogues. To address the problems of low natural abundance and limited synthetic methods for rare pentoses, biological synthesis has emerged recently as promising routes to these valuable compounds. This review summarizes enzymatic synthesis and whole cell microbial transformations of seven rare pentoses (L-ribulose, L-ribose, Lxylulose, L-xylose, L-lyxose, D-lyxose, D-xylulose) and two sugar alcohols (xylitol, L-arabinitol) as well as their interconversions. Examples of improving existing enzymes and discovering new systems are also discussed as advancements in genomics and bioengineering.
Keywords: microorganism